New corona-electrostatic separator with two coaxial vertical cylindrical electrodes for sorting conductors and non-conductors from granular mixtures - Fethi, Miloua; Miloudi, Mohamed; Medles, Karim; Zeghloul, Thami; Seddik, Touhami; Dascalescu, Lucian (Separation science and technology, 2025)
A major advance in the recycling of conductive and non-conductive materials contained in granular mixtures originating from industrial waste has been achieved thanks to the development of an innovative corona-electrostatic separator. The aim of this paper is to prove that the new device, equipped with two coaxial vertical cylindrical electrodes, offers a reliable and efficient solution for the selective sorting of copper and plastics from shredded small electrical cables waste. Careful control of operating parameters, such as voltage and air flow, is crucial to achieving optimum separation. Experiments conducted according to the response surface modeling methodology have shown that using a voltage of 30 kV and a flow rate of 1690 m 3 /min gives the highest recovery rates (beyond 90% for both products) and at purity levels of roughly 80% for plastics and 98% for copper. Further testing under various environmental conditions is recommended to assess the robustness of the electrostatic separation process.